Synthesis of nanostructured silica for use as a support for iron Fischer-Tropsch catalysts - Khoabane, Keneiloe (My University, 2008)
ABSTRACT Nanostructured silica materials were synthesised by the sol-gel process using simple hydroxyacids as template precursors, and these materials were employed as supports for a low temperature iron Fischer-Tropsch (FT) catalyst. Thus, this thesis is divided into two parts: (I) the synthesis of nanostructured silica gels, and (II) their use as catalyst supports in the FT reaction. PART I The effects of synthesis conditions, acidic and basic template precursors and their amounts, synthesis temperature, duration of hydrolysis and ageing, solvent concentration, organic co-solvent, and the synthesis procedure used on the morphology of the silica materials were studied. The synthesised silica gels were characterised by TEM, SEM, BET, TGA, and XRD. Mixtures of different morphologies were obtained with all the hydroxyacids used and the studies revealed that the morphology of the resultant silica gels was largely determined by the type of the hydroxyacid used. The use of oxalic acid produced materials with 4-9 % micropores and a mixture of meso- and macropores mainly consisting of hollow tubes and hollow spheres; the use of D-gluconic and L-tartaric acids produced mesoporous materials mainly consisting of hollow spheres and sheets with folds, respectively; while the use of stearic and cinammic acids produced macroporous materials mainly consisting of solid spheres and undeveloped particles, respectively. The silica gels formed were found to be amorphous in nature, despite the different morphologies that existed in them, and were also thermally stable.Studies involving the use of oxalic and D-gluconic acids showed that the key to the shape of the resultant morphologies resided in the shape of the template crystals formed in solution under specific synthesis conditions. The template shape depended on the type of the template precursor (i.e. both the acid and the base) and its amount. It was also observed that under certain conditions, both at elevated temperatures (≥ 55 oC) and at high water concentrations (> 50 %), the template dissolved and this led to low yields of shaped morphologies (i.e. hollow spheres and tubes). The solvent concentration to produce a maximum tube yield (in the case of oxalic acid) and hollow sphere yield (in the case of D-gluconic acid) was found to require about 25- 50 % water. Very well-developed tubes were also obtained at this concentration (i.e. with oxalic acid). Long hydrolysis and ageing times (i.e. > 2 h) of the sols and gels, respectively, resulted in the formation of surface attached colloidal particles and of tubes and hollow spheres with decreased wall thicknesses. Pre-formation of the template prior to addition of TEOS produced materials with lower surface areas, higher tube yields and bigger tube sizes when compared with materials synthesised by forming the template together with the silica gel. PART II Two types of silica gels were used as supports for an iron FT catalyst; the nanostructured silica gels (tubes with surface area 109 m2/g and spheres with surface area 245 m2/g ) and a commercial silica gel (Davisil silica, surface area 273 m2/g - consisting of undeveloped particles). The effect of varying the potassium promotion levels and of the support morphology on the catalyst activity and selectivity in the FT reaction was studied at 250 oC, in a slurry operated CSTR.It was observed that an increase in the potassium loading up to 0.5 wt % in the Davisil silica catalyst led to a decrease in the catalyst FT and water gas shift (WGS) activity, and methane selectivity. However, the efficiency of the catalyst to produce hydrocarbons increased with an increase in potassium loading up to 0.5 wt %. Increasing the potassium level up to 0.9 wt % led to a slight increase in both the catalyst activity and methane selectivity, and a decrease in the catalyst efficiency. For the silica tubes catalyst, increasing the potassium loading to 0.5 wt % led to an increase in the catalyst activity and methane selectivity, while increasing the potassium level up to 0.9 wt % led to a decrease in the catalyst activity. For both supports, increasing the potassium loading led to an increase in the selectivity towards high molecular weight hydrocarbons, olefins (relative to paraffins) and terminal olefins (relative to internal olefins). While the Davisil silica and the silica tube catalysts remained more or less stable throughout the reaction, the activity of the silica spheres catalyst declined rapidly with time. The nanostructured silica gel supported catalysts both showed higher activities and methane selectivities, but lower efficiencies when compared to the Davisil silica catalyst. Although the selectivity of all three catalysts towards olefins were similar, their selectivity towards high molecular weight hydrocarbons decreased in the order Davisil silica > silica spheres > silica tubes. Elongated needlelike Fe nanoparticles (NPs) were obtained in the silica tubes catalyst, semi hexagonal Fe NPs were formed in the silica spheres catalyst, while the Fe NPs could not be distinguished from the support in the Davisil silica catalyst. After the reaction, the surface areas of all three catalysts were found to have decreased and the catalysts to have sintered. The nanostructured silica supported catalysts showed the presence of Fe nanozones surrounded by a layer of amorphous carbon, while only agglomerated particles of Fe and some carbon rich regions were observed in the Davisil silica catalyst. No evidence of alteration of the morphology of the nanostructured silica supports was observed after the reaction.
Keywords: nanostructured silica; silica nanotubes; Fischer-Tropsch iron catalyst; silica hollow spheres